THE DIALECTIC STRENGTH IN SOCIAL CONSTRUCTION OF URBAN COMMUNITY FOR PREVENTING STUNTING DURING THE COVID-19 PANDEMIC - Yosi Arianti; Gita Isyanawulan; Diana Dewi Sartika; Soraida, Safira (Universitas Widya Mataram, 2023)
In Palembang, Indonesia, toddlers who suffer from stunting, a condition marked by a failure to develop, are the subject of this study. This study analyses and assesses the function of urban social construction in avoiding infant stunting during the first 1,000 days of life using a qualitative approach and Berger and Luckmann's theory of social construction. According to the study's findings, this social construction is influenced by socioeconomic elements like education, the surrounding community, and cleanliness, as well as the reality of pregnancy, delivery, and raising children. This study stresses the importance of dialectics in this social construction by demonstrating how clashes and interactions between social systems and people have an impact on efforts to prevent stunting. This work is groundbreaking because it recognises dialectics as a fundamental component of social construction that affects stunting prevalence and prevention. The dialectic offers fresh perspectives for preventing stunting in urban areas like Palembang and highlights the social factors that affect preventative efforts. Keywords: Social Construction; Urban Community; Stunting Prevention; Dialectic Strength